Auto-narrative Work as a form of Art Therapy and Contemporary Challenges - Olga Hucko-Biernat (Studia z Teorii Wychowania)
This article presents the assumptions, the aims, and the course of the author's project of art-therapeutic auto-narrative work as a form of an adult development support. The problem concerns proactivity and reflexivity of an individual facing various challenges. The article describes sociological concepts regarding human condition and proposes related definitions of the title challenges. The theoretical background of auto-narrative work is presented by referring to narrative and biographical learning, narrative identity, biographical work, and self-creation. A sketch of the art therapy process leading to increase the ability to better cope with everyday life and achieve self-awareness is outlined. The problem requires further study, research, and discussion of its applicability in practice.